Work-Leisure Conflict and Well-Being: The Role of Leisure Nostalgia. (19th May 2023) - Cho, Heetae
Abstract: Given the crucial importance of nostalgia in individuals' behavioral and psychological responses, this study measured the effect of leisure nostalgia on work-leisure conflict and subjective well-being. A total of 489 responses were collected from primary and secondary school teachers in Singapore, and this study conducted confirmatory factor analysis and structural equation modeling to analyze the data. Results showed that leisure nostalgia positively affected work-to-leisure conflict and subjective well-being, and work-to-leisure conflict had a negative effect on subjective well-being. However, relationships related to leisure-to-work conflict were shown to be insignificant. The findings of this study advance the theoretical knowledge of nostalgia in the contexts of leisure and occupational health psychology and contribute to school management in developing strategies and approaches for the betterment of teachers' well-being.